Forever Lulu - John, Kaye.; Corley, Annie; Joseph GordonLevitt; Lee Garlington; Patrick Swayze; Penelope Ann Miller; Richard Schiff; Melanie Griffith (Germany, USA Cinelulu Internationale Film production, 2000)
Lulu McAfee lives in a San Francisco home for mentally-ill adults. In June 1999, she bolts for L.A. and contacts Ben Clifton, an old flame, now unhappily writing for TV and unhappily married to a psychiatrist, Claire. Ben is ready to call Lulu's doctor when she tells him they have a son, born after she became ill and their affair ended. He calls Claire to tell her he's driving Lulu to Wisconsin to meet the boy on his 16th birthday, a visit Lulu claims is arranged. On the drive, Lulu tries to rekindle the affair and restart Ben's idealism. Meanwhile, Claire boards a plane to Madison to watch her marriage collapse. Is there really a son? What emotional landmines will the trip set off?
A schizophrenic romantic tracks down her college sweetheart to help her find their son she gave up for adoption sixteen years ago to the dismay of his new wife.
John Kaye
Languages: English, Turkish Subtitle: Turkish
Keywords: Romance; Comedy